Economic Theory and Socialist Economy: A Reply - Dobb, Maurice (Review of Economic Studies, 1935)
Journal Article Economic Theory and Socialist Economy: A Reply Get access Maurice Dobb Maurice Dobb Cambridge Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 2, Issue 2, February 1935, Pages 144–151, https://doi.org/10.2307/2967561 Published: 01 February 1935